Estimating realized relatedness in free-ranging macaques by inferring identity-by-descent segments - Annika Freudiger; Vladimir M. Jovanovic; Yilei Huang; Noah Snyder-Mackler; Donald F. Conrad; Brian Miller; Michael J. Montague; Hendrikje Westphal; Peter F. Stadler; Stefanie Bley; Julie E. Horvath; Lauren J. N. Brent; et al. (Proceedings of the National Academy of Sciences, 2025)
Biological relatedness is a key consideration in studies of behavior, population structure, and trait evolution. Except for parent–offspring dyads, pedigrees capture relatedness imperfectly. The number and length of identical-by-descent DNA segments (IBD) yield the most precise relatedness estimates. Here, we leverage different methods for estimating IBD segments from low-depth whole genome resequencing data to demonstrate the feasibility and value of resolving fine-scaled gradients of relatedness in free-living animals. Using primarily 4 to 6× depth data from a rhesus macaque ( Macaca mulatta ) population with long-term pedigree data, we show that we can infer the number and length of IBD segments across the genome with high accuracy even at 0.5× sequencing depth. In line with expectations based on simulation, the resulting estimates demonstrate substantial variation in genetic relatedness within kin classes, leading to overlapping distributions between kin classes. By comparing the IBD-based estimates with pedigree and short tandem repeat-based methods, we show that IBD estimates are more reliable and provide more detailed information on kinship. The inferred IBD segments also identify cryptic genetic relatives not represented in the pedigree and reveal elevated recombination rates in females relative to males, which enables the majority of close maternal and paternal kin to be distinguished with genotype data alone. Our findings represent a breakthrough in the ability to study the predictors and consequences of genetic relatedness in natural populations, contributing to our understanding of a fundamental component of population structure in the wild.